Modifikasi Firefly Algorithm Untuk Partial Shading pada Photovoltaic - Budiman; Machrus Ali (ALINIER: Journal of Artificial Intelligence & Applications, 2021)
Shadows of buildings or trees can partially cover the PV resulting in differences in solar radiation reception. Partial shading occurs when the PV module receives different solar radiation due to shadows of buildings or trees or clouds. This condition causes the output power of the PV array to decrease. Based on the PV curve, partial shading has a direct effect, so that a decrease in voltage or current causes a decrease in the output power of the PV. Because this requires a good control device. In this study, the method was compared without control (Uncontrolled), conventional PID (PID), PID tuned by Firefly Algorithm (PID-FA), and PID tuned by Modified Firefly Algorithm (PID-MFA). From the simulation results, it is found that the best voltage is obtained from the PID-MFA controller, the best voltage obtained from the PID-MFA controller is 1.2755 pu, the best current on the PID-MFA is 4,313; 3.67; 2,551 pu, and the maximum power is 3,253 pu. Thus it can be concluded that the best controller is PID-MFA. This research can later be used as a reference and other controllers are used to obtain an optimal controller.